2018
DOI: 10.22271/ortho.2018.v4.i1c.22
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of surgical management of tibial plateau fractures by locking compression plate

Abstract: Aim: To assess the clinical and functional outcome of surgically treated tibial plateau fractures with internal fixation by locking compression plated at SSIMS-RC, DAVANAGERE during JUNE 2015 TO FEBRUARY 2017. Objectives 1. To re-establish the anatomy of articular surface of upper end of tibia and knee joint perfectly by operative treatment with internal fixation. 2. To assess the radiological union of fractures after internal fixation with locking compression plate. 3. To assess the functional outcome of knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The present study revealed that, the minority of studied patients suffering from malunion. This result disagreed with (Siddesh et al, 2018) [9] who carried out A prospective study in department of orthopaedics, Ssims-Rc, Davanagere, Karnataka, India entitled as A prospective study of surgical management of tibial plateau fractures by locking compression plate which revealed that 10% of patients…”
Section: Regarding Measurement Of Quadriceps Muscle Strength;mentioning
confidence: 76%
“…The present study revealed that, the minority of studied patients suffering from malunion. This result disagreed with (Siddesh et al, 2018) [9] who carried out A prospective study in department of orthopaedics, Ssims-Rc, Davanagere, Karnataka, India entitled as A prospective study of surgical management of tibial plateau fractures by locking compression plate which revealed that 10% of patients…”
Section: Regarding Measurement Of Quadriceps Muscle Strength;mentioning
confidence: 76%